IMPLEMENTATION OF THE SIHALAL APPLICATION IN THE MINISTRY OF RELIGIOUS AFFAIRS OF BANDUNG CITY AS AN INNOVATION IN RELIGIOUS PUBLIC SERVICE DELIVERY (Al-Mubin, 2024)
The digitalization of halal certification has become increasingly important in strengthening the quality, accessibility, and responsiveness of religious public services in Indonesia. This study aims to analyze the implementation of SIHALAL at the Bandung City Office of the Ministry of Religious Affairs as an innovation in religious public service delivery. The study is grounded in perspectives on digital public service innovation, institutional capacity, and service implementation, which emphasize that technological systems generate public value only when supported by effective organizational practices. This research employs a qualitative approach with a case study design and relies on document analysis and relevant secondary data published up to 2023. The findings show that SIHALAL has functioned not merely as an administrative platform but as a service infrastructure integrating registration, verification, assistance, and certification processes. Its innovative value lies in improving access, procedural clarity, and service efficiency, although its effectiveness remains shaped by institutional capacity, coordination, and users’ procedural readiness